Legal Analysis of Witness and Victim Protection in Cases of Sexual Violence Crimes - Faruk Rumbu Rabani Raya Ente (SEAN Institute, 2025)
Cases of sexual violence are a serious issue that requires special attention in the criminal justice system, especially in relation to the protection of witnesses and victims. This protection is important to guarantee the rights of victims and support a fair and just law enforcement process. This study aims to analyze the legal aspects of witness and victim protection in the context of sexual violence in Indonesia. The method used is a normative juridical study with a legislative approach and a review of court decisions. The results of the study show that although there are regulations governing the protection of witnesses and victims, such as the Witness and Victim Protection Law, the implementation of such protection still faces various obstacles, including the psychological problems of victims, social stigma, and limited protection facilities. Therefore, there is a need to improve the understanding of law enforcement officials, support facilities, and more comprehensive policies to realize effective protection for witnesses and victims of sexual violence crimes. This study is expected to serve as a reference for policymakers and legal practitioners in strengthening legal protection mechanisms for witnesses and victims.